eNOS polymorphisms as predictors of efficacy of bevacizumab-based chemotherapy in metastatic colorectal cancer: data from a randomized clinical trial - Ulivi, Paola (J Transl Med, 2015)
BACKGROUND: Bevacizumab plus chemotherapy is a widely used therapeutic option for first-line treatment of metastatic colorectal cancer (mCRC). However, molecular predictors of bevacizumab efficacy have not yet been identified. We analyzed vascular endothelial growth factor (VEGF) and endothelial nitric oxide synthase (eNOS) polymorphisms in relation to response to bevacizumab. METHODS: Two hundred and thirty-seven patients with mCRC enrolled onto the phase III prospective multicentre randomized “Italian Trial in Advanced Colorectal Cancer (ITACa)” trial were evaluated. One hundred fourteen patients received chemotherapy plus bevacizumab (CT + B) and 123 received chemotherapy (CT) alone. Five single nucleotide polymorphisms (SNPs) (−2578, −1498, −1154, −634 and +936) for VEGF and 2 SNPs (−786, +894) and one variable number tandem repeat in intron 4 for eNOS were analyzed for each patient. The polymorphisms were assessed in relation to progression-free survival (PFS), objective response rate (ORR) and overall survival (OS). RESULTS: VEGF 936C/T, eNOS +894 G/T and VNTR were significantly correlated with outcome in CT + B patients, but not in CT-only patients. In particular, patients with a specific haplotype combination of the 2 eNOS polymorphisms (defined eNOS Haplo1/Haplo1 and eNOS Haplo 2/Haplo2) showed significantly longer PFS (15.0 vs 9.1 months, P = 0.001) and OS (34.5 vs 20.5 months P = 0.002), and a higher ORR (71 vs 45.9%, P = 0.013) than those with the other genotypes, respectively. CONCLUSIONS: Specific eNOS polymorphisms may be capable of identifying a subset of mCRC patients who are more responsive to bevacizumab-based chemotherapy. If confirmed, these results would permit individually tailored treatment with bevacizumab. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12967-015-0619-5) contains supplementary material, which is available to authorized users.